PSYCHOMETRIC PROPERTIES OF SCREENING FOR POST-TRAUMATIC STRESS DISORDER IN UKRAINIAN REFUGEES IN THE CONTEXT OF THE RUSSIAN-UKRAINIAN WAR DURING THE OUTBREAK OF COVID-19 - Komarevtseva, I.O.; Kazakov, V.Ye.; Verbytskyi, Ye.Yu.; Chernykh, Yu.A.; Balabanova, K.V.; Komarevtsev, V.N.; Cherednichenko, R.V. (World of Medicine and Biology, 2024)
It happened so that the war began in the midst of the COVID-19 pandemic. However, the effects of COVID-19 in war-time internally displaced persons have been understudied. The purpose of the study was to examine post-traumatic stress disorder symptoms among internally displaced persons in Ukraine who contracted COVID-19 during the 2022–2023 Russian invasion. In the study, we used stress tests to assess the level of perceived stress, resistance to stress and the presence of depression in internally displaced persons who recovered from COVID-19. Our study demonstrated that Primary Care Screening Scale-5 can be applied as a reliable screening measure of post-traumatic stress disorder symptoms in internally displaced participants during COVID-19.
Keywords: internally displaced persons; COVID-19. post-traumatic stress disorder symptom